Identification of Candidate Carboxylesterases Associated With Odorant Degradation in Holotrichia parallela Antennae Based on Transcriptome Analysis - Yi, Jiankun; Wang, Shang; Wang, Zhun; Wang, Xiao; Li, Gongfeng; Zhang, Xinxin; Pan, Yu; Zhao, Shiwen; Zhang, Juhong; Zhou, Jing-Jiang; Wang, Jun; Xi, Jinghui (Frontiers in Physiology, 2021)
Insects rely on their olfactory systems in antennae to recognize sex pheromones and plant volatiles in surrounding environments. Some carboxylesterases (CXEs) are odorant degrading enzymes (ODEs), degrading odorant signals to protect the olfactory neurons against continuous excitation. However, there is no report about CXEs in Holotrichia parallela, one of the most major agricultural underground pests in China. In the present study, twenty candidate CXEs were identified based on transcriptome analysis of female and male antennae. Sequence alignments and phylogenetic analysis were performed to investigate the characterization of these candidate CXEs. The expression profiles of CXEs were compared by RT-qPCR analysis between olfactory and non-olfactory tissues of both genders. HparCXE4, 11, 16, 17, 18, 19 and 20 were antenna-biased expressed genes, suggesting their possible roles as odorant degrading enzymes. HparCXE6, 10, 11, 13 and 16 showed significantly higher expression profiles in male antennae, whereas HparCXE18 was expressed more in female antennae. This study highlighted candidate CXE genes linked to odorant degradation in antennae, and provided a useful resource for the further work on the H. parallela olfactory mechanism and selection of target genes for integrative control of H. parallela.